Optimalisasi Kinerja Ruas Jalan Dengan Metode PKJI 2023 dan Aplikasi PTV Vissim - Pratma, Najwan; Aprianto, Rizal; Siswanto, Joko (Universitas Negeri Gorontalo, 2025)
The suboptimal performance of road segments is a major issue in the transportation system that causes congestion and a decrease in mobility efficiency. Kaliurang Road in Sleman Regency has poor road performance, resulting in disrupted inter-regional connectivity. Optimization of road segment performance is proposed through performance analysis and traffic engineering scenario simulation. PKJI 2023 is used to analyze performance and PTV Vissim 2025 is used for simulating the testing of 30 optimization scenarios. Data was collected through direct surveys and documentation from the Transportation Department. Simulation validation uses GEH for vehicle volume and MAPE for speed with an analysis of five variables (vehicle speed, travel time, vehicle density, occupancy rate, and relative delay). Scenario 30, with a combination of lane additions, road widening, removal of on-street parking, one-way systems, and vehicle type hour restrictions, resulted in the best optimization with an 11.57% increase in speed, a 30.93% reduction in travel time, a 67.74% reduction in density, a 64.76% reduction in occupancy rate, and a 92.66% reduction in relative delay. The optimization results can be used as a strategic step for stakeholders in formulating policies to improve road segment performance to support sustainable inter-regional connectivity.